(untitled) (CIPEEX, 2026)
This paper addresses the issue of urban solid waste (MSW) generated by urbanization and global development, as well as its improper disposal, which causes significant environmental impacts. Our objective is to address the environmental assets and liabilities of the Anápolis/GO landfill and associated municipalities under its management, verifying their compliance with the guidelines of the National Solid Waste Policy established by Law No. 12,305 of August 2, 2010. We will use Environmental Accounting methodologies to calculate the environmental assets and liabilities of the Anápolis landfill and Environmental History to analyze the data historically, from 2010 to the present. Keywords: environment; environmental history; environmental accounting; Anápolis/GO landfill.